Relationships between habitual cadence, footstrike, and vertical load rates in runners - Futrell, E. E.; Jamison, S. T.; Tenforde, A. S.; Davis, I. S. (Medicine & Science in Sports & Exercise, 2018)
Excessive vertical ground reaction force (VGRF) load rates have been linked with running injuries. Increasing cadence (CAD) has been shown to reduce load rates; however, relationships between habitual cadence and load rates across a population of runners have not been examined.